Evaporative Cracking Characteristics of the Embankment Soil Affected by the Saline Concentration - Jiawei Liu; Yingzhi Xia; Hui Li; Guoping Hu; Mingming Hu (Advances in Civil Engineering)
Embankment soil affected by saline can not only cause roadbed settlement, frosting, and road cracks but also cause corrosion and cracking of roadbed pipelines, which seriously affects the stability of the road. Water evaporation and dry cracking of the saline soil mainly cause soil swelling, poor water stability, and corrosive characteristics of the embankment soil. In this study, the evaporative cracking characteristics of soil with different saline concentrations were investigated. The results showed that the moisture content decreased linearly with the drying time in the early evaporation process, subsequently decreased slow down in the mid-term evaporation, and finally become got and remain a residual moisture content, which are 46.39%, 44.05%, 42.70%, and 40.27% with the increase of the saline concentration. The evaporation process with different saline concentrations in the soil can be divided into three stages: uniform evaporation stage, slow down evaporation stage, and equilibrium evaporation stage, which was consistent with the moisture content change. With the development of the drying time, the cracks gradually appeared on the soil surface, gradually deepened in the soil, and expanded the crack network. The development of cracks can be divided into three stages: the cracking preparation stage, the crack development stage, and the crack stable stage. The cracking began at high evaporation rate under high saline concentration, and the fractal dimension remained stable under similar saline concentration. The fractal dimension was gradually increased with the decrease of the moisture content and the increase of the saline concentration, respectively. The soil began to crack with larger moisture under high saline concentration. The drying cracks in the nature were consistent with the configuration of the cracks formed in the experimental results.